Human Resource Competence and Fintech Adoption among Maluku MSMEs: Digital Literacy as Mediator - Pieter Novry Ruddy Rehatta; Hansen Rumtutuly (Westscience Press, 2026)
Despite the rapid development of financial technology (fintech), its adoption among micro, small, and medium enterprises (MSMEs) in archipelagic regions remains uneven due to differences in human resource capacity and digital readiness. This study analyzes the effect of human resource competence on fintech adoption among MSMEs in Maluku Province, with digital literacy as a mediating variable. The study employs a quantitative explanatory approach using primary data collected from 230 MSME actors through structured questionnaires. The data were analyzed using Partial Least Squares–based Structural Equation Modeling (SEM-PLS) to examine both direct and mediating relationships among variables. The results show that human resource competence has a positive and significant effect on digital literacy (β = 0.672; p < 0.001) and on fintech adoption (β = 0.429; p < 0.001). In addition, digital literacy has a positive and significant effect on fintech adoption (β = 0.512; p < 0.001) and partially mediates the relationship between human resource competence and fintech adoption. These findings indicate that digital literacy plays an important mechanism that enables human resource competencies to be translated into the utilization of digital financial technologies. Theoretically, this study extends the perspectives of Resource-Based View and Human Capital by demonstrating the mediating role of digital literacy in technology adoption among MSMEs. Practically, the results emphasize the importance of integrating human resource competence development with digital literacy enhancement to accelerate fintech adoption and support MSME digital transformation, particularly in archipelagic regions with limited digital infrastructure such as Maluku.